Characterization of Bacillus and Lactobacillus Encapsulated in Various Carrier Materials for Vannamei Probiotics (Litopenaeus vannamei Boone, 1931) - Yuli Andriani; Aufa Aulia Kanza; Mia Miranti Rustama; Ratu Safitri (JURNAL PERIKANAN DAN KELAUTAN, 2017)
Bacillus and Lactobacillus are bacteria that can be used in dry-stock probiotics in vannamei shrimp feed. In this study, it was performed to encapsulate Bacillus and Lactobacillus probiotic bacteria in several carrier materials, including rice flour, talc, and maltodextrin. The purpose of this study was to determine the type of carrier material that can provide the best probiotic character in the encapsulation process which will then be used in vannamei shrimp feed. The method used in this study is experimental method. The study was conducted with the preparation stage and the initial probiotic characterization test. Furthermore, Bacillus and Lactobacillus probiotic encapsulation process used spray drying method to produce powder inoculum, as well as advanced characterization test of bacteria that have been encapsulated. The parameters observed were the viability, resistance to temperature, pH and bile salts. Data were analyzed using ANAVA and Duncan Multiple Range Test. The results showed that all types of carrier materials used maintained the probiotic character of Bacillus and Lactobacillus after the encapsulation process. This can be seen from the character of probiotics that are in good category and deserve to be used as a probiotic agent after encapsulation process in the material of rice flour, maltodextrin, and talc.